Fodder legumes technology and farmer to farmer extension: a case of Desmodium and Calliandra in central Kenya - Sinja, J.; Karugia, Joseph T.; Mwangi, David Miano; Baltenweck, Isabelle; Romney, Dannie L. (International Livestock Research Institute, 2004)
Adoption studies on fodders legume technologies have shown that spread of the technology is significantly enhanced by informal methods of dissemination especially farmer-to-farmer extension. It is not known which type of farmers are involved in this dissemination. The objective of this study was to identify farm and farmer characteristics that influence farmer-to farmer extension hence identify the type of farmers that can disseminate fodder legume technologies. A random sample of 130 farmers who had been given calliandra in central Kenya responded to a structured questionnaire. Information collected included farm and farmer characteristics and the number of farmers the original farmer had given Calliandra outside the original group. A tobit model was used to analyze the data to get the magnitude of the effects of factors affecting the probability and the intensity of giving out the fodder. Results showed that farmers with positions in farmer groups** , community responsibility**, larger amounts of desmodium on the their farms** , more years of the fodder on their farms***; low access to markets* and off farm income* , were positively involved in spread of the fodder legume. It was recommended that this type of farmers be targeted with support to increase spread of the technology.